Evolutionary Application Service Providing (eASP). Ein Ansatz der Softwarebereitstellung - Jackewitz, Iver (Hamburg University Press, 2006)
This study deals with the provision of software and develops an approach to the analysis and design of software deployment contexts in which software is provided centrally for many. The provision of the web-based cooperation platform CommSy in two different constellations exemplifies the necessity of such a software supply approach for understanding and designing software supply contexts. The present work provides the foundation for the business model Application Service Providing and its extension to the software provisioning approach eASP (evolutionary Application Service Providing). The business model can thus be used for IT. Through eASP, the effects and services of software provision can be taken into account in the evolutionary and participatory software development and IT-supported organization design. eASP is not understood as a model of software provision, but as a pattern that helps to understand and design a concrete software provision.